Association of triglycerides/high density lipoprotein cholesterol ratio with insulin resistance in polycystic ovary syndrome - Karli, Sreenivasulu; V. S., Kiranmayi; Namburi, Rajendra Prasad; Bitla, Aparna Rajeshwar Rao; Sachan, Alok (International Journal of Research in Medical Sciences, 2018)
Background: Insulin resistance (IR) is frequently observed in women with polycystic ovary syndrome (PCOS). Recent studies advocated that triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C) can be used as a simple clinical indicator of IR. Hence, the present study was performed to investigate the use of TG/HDL-C and its association with IR in PCOS. Methods: Forty-one patients with PCOS and 40 healthy age matched women were randomly enrolled. Demographic and clinical characteristics were obtained. Insulin resistance was defined by the homeostasis model assessment for insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI). Results: In PCOS group, the insulin, HOMA-IR and TG/HDL-C ratio were significantly higher (p=0.001) than controls while, QUICKI was lower (p=0.001). Insulin, HOMA-IR were positively correlated with TG/HDL-C (ρ=0.303, p=0.006 and ρ=0.312, p=0.005 respectively) while, QUICKI was negatively correlated (ρ=-0.698, p=0.001). In receiver operating characteristic (ROC) analysis, area under the curve (AUC) for model based on QUICKI levels was better 0.898 (95% CI: 0.811-0.955, p=0.001) than HOMA-IR 0.636 (95% CI: 0.522-0.740, p=0.03). A cut-off value 3.23 for TG/HDL-C is proposed from the model based on QUICKI with best combination of sensitivity 83.3% and specificity 86.7%. Conclusions: Results of present study support that TG/HDL-C ratio may be a simple indicator of IR in PCOS patients which helps clinicians to identify IR in small centers, where the assays for insulin measurement are not available.